PEMAKAIAN CHELATING MONOLITH SEBAGAI SOLID PHASE MICROEXTRACTION (SPME) TRACE ELEMEN DI DALAM AIR - Dwinna Rahmi (Universitas Andalas, 2009)
Â ABSTRACTÂ AÂ syringe-basedÂ sampleÂ pretreatmentÂ tool,Â namedÂ hereinÂ â€œchelatingÂ monolithâ€,Â hasÂ beenÂ developedÂ forÂ simpleÂ andÂ facileÂ solidÂ phaseÂ microextractionÂ (SPME)Â ofÂ traceÂ elementsÂ inÂ naturalÂ waters.Â TheÂ monolithÂ wasÂ directlyÂ preparedÂ withinÂ theÂ confinesÂ ofÂ aÂ commerciallyÂ availableÂ syringeÂ filterÂ tipÂ byÂ aÂ two-stepÂ process:Â 1)Â inÂ situÂ polymerizationÂ ofÂ glycidylÂ methacrylateÂ (GMA)Â withÂ ethyleneÂ glycolÂ dimethacrylateÂ (EDMA)Â andÂ 2)Â subsequentÂ modificationÂ withÂ iminodiacetateÂ (IDA)Â viaÂ ringÂ openingÂ reactionÂ ofÂ epoxide.Â TheÂ compositionÂ ofÂ porogenicÂ solventÂ wasÂ firstÂ optimizedÂ toÂ makeÂ aÂ rigid-porousÂ materialÂ thatÂ hasÂ highÂ permeabilityÂ andÂ ampleÂ surfaceÂ areaÂ asÂ muchÂ asÂ possible.Â Then,Â theÂ pHÂ andÂ concentrationÂ ofÂ theÂ IDAÂ modificationÂ solutionÂ wereÂ examinedÂ toÂ obtainÂ higherÂ chelatingÂ capacity.Â TheÂ metalÂ adsorptionÂ propertiesÂ ofÂ theÂ obtainedÂ chelatingÂ monolithÂ wereÂ evaluatedÂ throughÂ anÂ adsorption/desorptionÂ experiment.Â AfterÂ optimizationÂ ofÂ someÂ parametersÂ suchÂ asÂ sampleÂ solutionÂ pH,Â eluentÂ concentrationÂ andÂ theÂ volume,Â goodÂ recoveriesÂ ofÂ moreÂ thanÂ 80%Â wereÂ obtainedÂ forÂ 28Â elementsÂ includingÂ REEs,Â Fe,Â Co,Â Ni,Â Cu,Â Zn,Â Ga,Â PbÂ andÂ ThÂ inÂ aÂ singleÂ extractionÂ step.Â TheÂ proposedÂ SPMEÂ methodÂ wasÂ validatedÂ throughÂ theÂ analysisÂ ofÂ riverÂ waterÂ certifiedÂ referenceÂ materialÂ (CRM:Â JSACÂ 0301-1)Â Keywords:Â SolidÂ phaseÂ microextraction;Â syringeÂ filter;Â chelatingÂ monolith;Â iminodiacetate;Â ICP-MS